Assessing abrasion of orthodontic surface sealants using a modified ophthalmic optical coherence tomography device - Şen, Sinan; Erber, Ralf; Kunzmann, Kevin; Kirschner, Stefanie; Weyer, Vanessa; Schilling, Lothar; Rues, Stefan; Orhan, Gül; Lux, Christopher J.; Zingler, Sebastian (Clinical oral investigations, 2018)
Objective: Optical coherence tomography (OCT) is a clinical standard in ophthalmology. Currently, its application in dentistry is gaining increasing interest. In this study, we tested the possibility to use a modified commercially available spectral domain OCT (SD-OCT) to assess the layer thickness of orthodontic surface sealants. Materials and methods: Reference samples of surface sealants for calibration and repeatability testing were measured using a micrometer screw. SD-OCT measurements were compared with micro-CT and light microscopic analyses. After validating the calibration of the SD-OCT, surface sealant layer thickness after aging (thermo cycling) and simulation of professional tooth cleaning (PTC) was assessed using the SD-OCT on 45 extracted teeth assigned to three test groups (n = 15 each): Light Bond™ Sealant, Pro Seal®, and Opal® Seal. Results: SD-OCT showed excellent repeatability and accuracy for measurements of surface sealant layer thickness. Compared with micro-CT, SD-OCT showed better accordance with the reference measurements. The analysis of surface sealants after thermo cycling and PTC revealed poor resistance of Light Bond after only aging and demonstrated substantial wear of all sealants after aging and PTC.ConclusionImaging using commercially available ophthalmic SD-OCT might represent a suitable non-invasive methodology for longitudinal assessments of surface sealant layer thickness in vitro and in vivo. Clinical relevance: SD-OCT might be a suitable non-invasive method for longitudinal assessments of surface sealant durability in clinical trials.